Analysis of Soil Bearing Capacity in Kauman, Tulungagung as a Subgrade For Flexible Pavement - Fathurrohman, Nadi Rheiza; Cahyono, Andri Dwi; Sefiyanti, Redyka; Pasya, Salman Alfaridh; Oktabernandus, Satria Perdana; Qalby, Atsfiela Dzulkhan; Ichwan, Zainal (CIVED, 2024)
This research aims to evaluate the bearing capacity of the soil in Kates Village, Kauman District, Tulungagung Regency, as a subgrade in flexible pavement through California Bearing Ratio (CBR) testing in the Civil Engineering Laboratory of Kadiri University. The tests were conducted with 56, 25, and 10 blows to determine their impact on the soil's density, strength, and stability. The results showed that soil with 56 blows had the highest CBR value of 28.660% at a 5.08 mm penetration, indicating excellent bearing capacity. The soil with 25 blows showed a CBR value of 17.060%, which is quite high, ensuring adequate stability and bearing capacity. Conversely, the soil with 10 blows had the lowest CBR value of 4.094%, indicating the need for additional compaction before being used in road construction. This research confirms that the number of blows has a significant impact on soil quality, with more intensive compaction improving the soil's density and stability. The final design CBR value obtained was 16%, leading to the conclusion that the soil in this area can be used as a subgrade for flexible pavement.